Effect of morphology of C-rich silicon carbonitride ceramic on electrochemical properties of sulfur cathode for Li-S battery. (10th July 2021) - Qu, Fangmu; Graczyk-Zajac, Magdalena; Vrankovic, Dragoljub; Chai, Nan; Yu, Zhaoju; Riedel, Ralf
Abstract: Porous conducting materials represent a promising support for the immobilization of sulfur in the cathode of lithium–sulfur (Li-S) batteries. Herein, we provide an easy and scalable procedure for the preparation of such cathodes. This strategy consists of an infiltration of sulfur under solvothermal conditions at 155 °C into pores of carbon-rich silicon carbonitride (C-rich SiCN). Porous polymer-derived SiCN ceramics possess a unique combination of high electronic conductivity and robust, stress accommodating mechanical properties. The impact of the initial porosity and elemental composition of SiCN ceramics on the electrochemical performance of SiCN-S composites is addressed in this work. It is shown that material pyrolyzed at 1000 °C revealing a mesoporous character in line with the presence of a free carbon phase dispersed in SiCN demonstrates the best electrochemical stability and the highest capacity (more than 310 mAh/g over 40 cycles) at a high sulphur content of 66 wt.%.